Pengembangan Aplikasi Absensi Berbasis Web Untuk Work From Home (WFH) Pada Bawaslu Kota Malang - Faiq Zafi (PT. Hasba Edukasi Mandiri, 2025)
The web-based attendance application for Work From Home (WFH) at Bawaslu Kota Malang was developed to enhance the efficiency and accuracy of employee attendance recording. This system is designed with key features such as location-based attendance, attendance verification through photo uploads, and real-time automated attendance recapitulation. The web-based technology enables the application to be accessed across various devices, including computers and mobile phones, providing greater flexibility for users. The application development utilizes the CodeIgniter framework for the backend, along with HTML, CSS, and JavaScript for the frontend. MySQL serves as the primary database, while the Black Box Testing method was applied to ensure all features function properly. The testing results indicate that the application operates stably and meets user requirements without critical bugs. System evaluation and maintenance are carried out periodically to improve performance and align with organizational needs. With the implementation of this application, the attendance system at Bawaslu Kota Malang has become more transparent, effective, and flexible, while also reducing reliance on previously used paid applications. This application is expected to provide a cost-effective and efficient solution in supporting WFH policies.